Towards the Development of Microbial Ecotoxicology Testing Using Chlorpyrifos Contaminated Sediments and Marine Yeast Isolates as a Model - Gustavo Echeverri-Jaramillo; Beatriz Jaramillo-Colorado; Howard Junca; Claudia Consuegra-Mayor (Microorganisms, 2022)
Chlorpyrifos (CP), a widely used pesticide, and its metabolite 3,5,6-trichloro-2-pyridinol (3,5,6-TCP), are xenobiotic compounds detected in many biomes, notably in marine sediments, all over the world. These compounds are posing a serious environmental and health problem given their toxicity to wildlife and possible exposure effects to human neurodevelopment. Microorganisms at CP-impacted environments could harbor metabolic capabilities that can be used as indicators of the biological effects of the contaminant and could encode selected functions reactive against contaminants. Those features could be used for microbial ecotoxicology applications by collectively using analytical, enzymatic, microbiological and toxicological techniques in order to assess the biological effects of pollutants and other environmental/climatic stressors in ecosystems. The objective of this study was to assess the variability in the metabolic responses of yeast isolates from CP-contaminated marine sediments as potential biological indicators for microbial ecotoxicology testing. Sediment samples from a South Caribbean tropical shore (Cartagena Bay, Colombia) were collected, and deoxyribonucleic acid (DNA) was recovered from lyophilized aliquots. The DGGE (Denaturing Gradient Gel Electrophoresis) technique targeting fungal Internal Transcribed Spacer (ITS) showed the great diversity of fungal types. Simultaneously, yeast strains were isolated from the freshly collected sediment samples. Physiological characterization including API 20C and antibiosis tests, growth patterns at salt concentrations (2/4/10/25%), temperatures (4/25/37/45 °C), esterase activity assay and resistance tests to CP/TCP toxicity resulted in 10 isolated yeast strains, identified as Candida spp. (6), Cryptococcus spp. (3). and Rhodotorula spp. (1), showing promising characteristics to be used as a test for yeast-based ecotoxicity indicators. The patterns of carbohydrate assimilation, low antibiosis, presence of esterases/lipases, growth in a wide range of temperatures and salt concentrations, and tolerance to minimal inhibitory concentrations of CP and TCP are factors useful for testing environmental samples.